INFLUENCE MODELS OF ENTREPRENEURIAL ORIENTATION, ENTREPRENEURSHIP TRAINING, AND BUSINESS PERFORMANCE OF SMALL MEDIUM ENTERPRISES - Ade Octavia; Zulfanetti Zulfanetti; Erida Erida (Jurnal Sains Sosio Humaniora, 2017)
Purpose-the increasing of SME number in Indonesia is not followed by the increasing of business performance, although various managerial and entrepreneural tranings, as well as busniness advocations has been given intensively by government. The objective of this research is to analise the impact of entrepreneural orintation, market orientation, managerial skill,and entrepreneurship training on SMEs business performance. Design/methodology/ approach- the approach used is survey method. Data gathered from 200 respondents accross for districts or city in Jambi Province, and Structural Equation Modelling (SEM) used as analysing tool. Findings- this research find that the business performance is influenced by the level of entrepreneural orientation and the attending of entrepreneurship training. Management skill is the intervening variable between entrepreneurship traning and business performance. The result also find that market orientation is an intervening for the relationship between entrepreneural orientation and business performance.